2005
DOI: 10.1136/jcp.2004.016972
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of adherens and tight junctional molecules in normal animal larynx; determining a suitable model for studying molecular abnormalities in human laryngopharyngeal reflux

Abstract: Background: The disruption of intercellular junctions in the larynx is a pathological feature of laryngopharyngeal reflux (LPR). Good experimental models are necessary to gain greater insight into the molecular mechanisms and alterations that result from abnormal exposure of the laryngeal epithelium to acid refluxate. Aims: To characterise laryngeal tissues from different species to determine the most suitable for use in experimental studies of LPR. Methods: Human and non-human laryngeal tissues (mouse, rat, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…10 Adherens junctions and desmosomes were also observed consistent with their presence in humans. [10][11][12] However, despite the presence of intercellular …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Adherens junctions and desmosomes were also observed consistent with their presence in humans. [10][11][12] However, despite the presence of intercellular …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in addition to demonstrating an epithelial phenotype, candidate tissue constructs must also demonstrate the presence of important components of the epithelial barrier, including intercellular junctions. The native vocal fold epithelium contains intercellular junctions, including tight junctions, 10,11 gap junctions, 12 adherens junctions, 11 and desmosomes. 10 While Long and colleagues 9 reported the presence of e-cadherin, a marker of adherens junctions, in their model, further evidence of intercellular junctions was not provided.…”
Section: Introductionmentioning
confidence: 99%
“…The cytoplasmic tails of cadherins bind members of the armadillo protein family, such as β-catenin. Cadherins communicate with the actin cytoskeleton through contacts with β-catenin (7).…”
Section: Introductionmentioning
confidence: 99%
“…The authors indicated that the porcine larynx was a superior model for research of epithelial damage occurring during LPR. 21 In the present study, Bama minipigs were used. The miniature pig has been widely accepted as the experimental animal.…”
Section: Discussionmentioning
confidence: 99%
“…The Bama minipigs were 4-6 months old, the mean weight was 10 kg, and the mean length was 71 cm. Minipigs were maintained in a pathogen-free environment with a 12:12-hour light-dark cycle, temperature (20)(21)(22) o C) and humidity (50-60%) for 1 week prior to experiment in order to adapt to environment. Ten Bama minipigs were randomly divided into control group and stent group.…”
Section: Animalsmentioning
confidence: 99%